Comparative analysis of confocal microscopy on fresh breast core needle biopsies and conventional histology - C. Elfgen; B. Papassotiropoulos; Z. Varga; L. Moskovszky; M. Nap; U. Güth; A. Baege; E. Amann; F. Chiesa; C. Tausch (BMC, 2019)
Abstract Background Evaluation of core needle biopsies (CNB) is a standard procedure for the diagnosis of breast cancer. However, tissue processing and image preparation is a time- consuming procedure and instant on-site availability of high-quality images could substantially improve the efficacy of the diagnostic procedure. Conventional microscopic methods, such as frozen section analysis (FSA) for detection of malignant cells still have clear disadvantages. In the present study, we tested a confocal microscopy scanner on fresh tissue from CNB with intention to develop an alternative device to FSA in clinical practice. Patients and methods In 24 patients with suspicious breast lesions standard of care image-guided biopsies were performed. Confocal images have been obtained using the Histolog™ Scanner and evaluated by two independent pathologists. Hematoxylin-Eosin (H&E) histological sections of the biopsies were routinely processed in a blinded fashion with respect to the confocal images. Results In total 42 confocal images were generated from 24 biopsy specimens, and available for analysis within a few minutes of taking the biopsy. This resulted in 2 × 42 = 84 pathologic evaluations. In four cases, a pathologic diagnosis was not possible with confocal microscopy. An exact correlation based on the B-classification was reached in 41 out of 80 examinations and in another 35 cases in a broader sense of correspondence definition (i.e. malignant vs. benign). Conclusions As a reliable on-site method, the Histolog™ Scanner provides a visualization of cellular details equivalent to the H&E standards, permitting rapid and accurate diagnosis of malignant and benign breast lesions. Furthermore, this device offers great potential for immediate margin analysis of specimen in breast conserving therapy.